Biogenic Synthesis of Magnetite Nanoparticles Using Leaf Extract of Thymus schimperi and Their Application for Monocomponent Removal of Chromium and Mercury Ions from Aqueous Solution. (15th April 2022) - Geneti, Sintayehu Tamenne; Mekonnen, Gemechis Asfaw; Murthy, H. C. Ananda; Mohammed, Endale Tsegaye; Ravikumar, C. R.; Gonfa, Bedasa Abdisa; Sabir, Fedlu Kedir
Abstract : Currently, plant templated synthesis of magnetite iron oxide nanoparticles (Fe3 O4 NPs) was emerged for multifunctional purposes. In this study, the leaf extract of the plant Thymus schimperi was utilized to synthesize Fe3 O4 NPs. The synthesized NPs were characterized by using technical tools such as X-ray diffraction (XRD) spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy-energy dispersive X-ray (SEM-EDX) analysis, and ultraviolet-visible (UV-Vis) spectroscopy, and thermal analysis (TGA-DTA). The XRD result corroborated the presence of desired phase formation having pure cubic face centered phase structure with average crystallite particle size ranging from 20 nm to 30 nm. SEM micrographs confirmed microstructural homogeneities and remarkably different morphology of Fe3 O4 NPs. Mercury (II) and chromium (VI) removal efficiencies of Fe3 O4 NPs were found to be 90% and 86% from aqueous solution at initial concentration of 20 mg/L, respectively. Various factors which affect the metal ion removal efficiency such as metal ion initial concentrations, pH, contact time, and adsorbent dosage were also studied. The optimum pH and contact time for chromium ion adsorption were pH 5 and 60 min and that of mercury were observed to be pH 7 and 90 min, respectively. The Langmuir isotherm was best fitted for sorption of Hg(II) ion, and the Freundlich isotherm was best fitted with sorption of Cr(VI) ion onto the surface of Fe3 O4 NPs. The mechanism of adsorption of both Hg(II) and Cr(VI) ions was obeyed pseudo 2 nd order kinetics. The recorded percent removal efficiencies revealed that these Fe3 O4 NPs synthesized through leaf extract of the plant called Thymus schimperi have demonstrated excellent potentiality in the remediation of heavy metal ions. The synthesized Fe3 O4 NPs were regenerated (reused) for adsorptive removal of Hg(II) and Cr(VI) for five consecutive cycles without significant loss of removal efficiency. Fe3 O4 NPs were reused with only 4.17% loss of removal efficiency against Hg(II) and only 3% loss of removal efficiency against Cr(VI) metal ions.